2021
DOI: 10.3389/fonc.2021.700204
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of CT- and MRI-Based Texture Analysis and Imaging Findings for Grading Cartilaginous Tumors in Long Bones

Abstract: ObjectiveTo confirm the diagnostic performance of computed tomography (CT)-based texture analysis (CTTA) and magnetic resonance imaging (MRI)-based texture analysis for grading cartilaginous tumors in long bones and to compare these findings to radiological features.Materials and MethodsTwenty-nine patients with enchondromas, 20 with low-grade chondrosarcomas and 16 with high-grade chondrosarcomas were included retrospectively. Clinical and radiological information and 9 histogram features extracted from CT, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…A clinical validation of the radiomics-based prediction model was reported in 38 (69%) of the 55 studies. In 22 (40%) studies, it was performed on a separate set of data from the primary institution, namely the internal test dataset, which was chosen randomly [ 19 , 20 , 24 , 28 , 29 , 31 , 32 , 37 , 41 , 42 , 45 , 47 , 52 , 53 , 59 , 65 , 66 , 68 ], based on temporal criteria [ 61 , 69 , 70 ] or different acquisition scanners [ 62 ]. Of note, in a multi-center study, patients were split into training and test cohorts randomly rather than following geographical criteria [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…A clinical validation of the radiomics-based prediction model was reported in 38 (69%) of the 55 studies. In 22 (40%) studies, it was performed on a separate set of data from the primary institution, namely the internal test dataset, which was chosen randomly [ 19 , 20 , 24 , 28 , 29 , 31 , 32 , 37 , 41 , 42 , 45 , 47 , 52 , 53 , 59 , 65 , 66 , 68 ], based on temporal criteria [ 61 , 69 , 70 ] or different acquisition scanners [ 62 ]. Of note, in a multi-center study, patients were split into training and test cohorts randomly rather than following geographical criteria [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that HU measurements on CT scans can serve as a tool to differentiate between enchondroma and ACT, reflecting the characteristics of the tumor matrix. This aspect will be further analyzed in the future with a larger sample size and additional tools such as texture analysis [ 30 , 31 , 32 , 33 ]. It is also notable that, in the combined modality of SPECT/CT, both radiotracer and radiodensity information can be obtained simultaneously without additional examinations.…”
Section: Discussionmentioning
confidence: 99%
“…However, DWI cannot differentiate low-grade lesions from high-grade chondrosarcomas [ 72 ]. Thus, novel tools for the objective grading of chondrosarcomas have recently been introduced, including texture analysis [ 73 , 93 ] and radiomics [ 94 ] with quantitative analysis. Deng et al [ 93 ] reported that CT-based texture analysis showed potential for the grading of cartilaginous tumors in long bones.…”
Section: Diagnostic Dilemma Of Chondrosarcoma Classificationmentioning
confidence: 99%
“…Thus, novel tools for the objective grading of chondrosarcomas have recently been introduced, including texture analysis [ 73 , 93 ] and radiomics [ 94 ] with quantitative analysis. Deng et al [ 93 ] reported that CT-based texture analysis showed potential for the grading of cartilaginous tumors in long bones. Gitto et al [ 94 ] reported that their machine-learning approach showed satisfactory diagnostic performance for the classification of low-to-high-grade cartilaginous bone tumors based on radiomic features extracted from unenhanced MRI.…”
Section: Diagnostic Dilemma Of Chondrosarcoma Classificationmentioning
confidence: 99%